A Simple and Highly Effective Ligand System for the Copper(I)‐Mediated Assembly of Rotaxanes1. Issue 50 (14th October 2014) - Campbell, Christopher J.; Leigh, David A.; Vitorica‐Yrezabal, Inigo J.; Woltering, Steffen L.
Abstract A [2]rotaxane was produced through the assembly of a picolinaldehyde, an amine, and a bipyridine macrocycle around a CuI template by imine bond formation in close‐to‐quantitative yield. An analogous [3]rotaxane is obtained in excellent yield by replacing the amine with a diamine, thus showing the suitability of the system for the construction of higher order interlocked structures. The rotaxanes are formed within a few minutes simply through mixing the components in solution at room temperature and they can be isolated through removal of the solvent or precipitation.